O Impacto das Habilidades Sociais para a Depressão em Estudantes Universitários - Bolsoni-silva, Alessandra Turini; Loureiro, Sonia Regina (Instituto de Psicologia, Universidade de Brasília, 2016)
ABSTRACT Depression is prevalent in university students, and there is a gap in relation to studies about social skills associated to depression. The objective of this study was to compare the social skills and the perceptions of consequences in interactions of students with depression (n=64), compared to a non-clinical group (n=64), and verify the predictive value of social skills. Social skills and mental health were measured by validated instruments. Significant differences in communication, affection, expressing negative feelings, dealing with criticism and public speaking were found. The group with depression reported more negative consequences and feelings in social interactions. Regression analysis identified that a deficient repertoire of social skills was predictor of depression, what suggests the relevance of prevention and intervention programs for this population.

RESUMO A depressão é prevalente em universitários, embora se verifique escassez de estudos sobre habilidades sociais associadas à depressão. Objetivou-se comparar as habilidades sociais e as percepções de consequências nas interações de universitários com depressão (n=64) em relação a um grupo não clínico (n=64); e verificar o valor preditivo das habilidades sociais. Habilidades sociais e saúde mental foram mensuradas por instrumentos aferidos. Constatou-se diferenças significativas em comunicação, afeto, expressar sentimentos negativos, lidar com críticas e falar em público. O grupo com depressão relatou mais consequências e sentimentos negativos nas interações sociais. Na análise de regressão identificou-se que um repertório deficitário de habilidades sociais foi preditor de depressão, o que sugere a relevância de programas de prevenção e intervenção para essa população.
The Impact of Social Skills on Depression of University Students
Keywords: social skills; university students; mental health; depression; prevention; habilidades sociais; universitários; saúde mental; depressão; prevenção